Stock Selection dan Market Timing Ability Reksa Dana Syariah Saham di Indonesia - Fadiyah Hani Sabila (Universitas Sulawesi Barat, 2019)
The purpose of this research is to know investment manager’s ability on stock selection and market timing of Indonesia sharia equity mutual funds on 2015-2017. Number of sample that use in this research is 15 sample with purposive sampling method. Data analysis technique used is Treynor-Mazuy condition regression model using panel data. This research method using panel data analysis test that is test Chow, Hausman, and Lagrange Multiplier. The result showed that the model chosen is a random effect models. F test and T test results indicate that investment manager’s of Indonesia sharia equity mutual funds have stock selection and market timing ability.